2018
DOI: 10.3389/fnins.2018.00450
|View full text |Cite
|
Sign up to set email alerts
|

Altered Spontaneous Regional Brain Activity in the Insula and Visual Areas of Professional Traditional Chinese Pingju Opera Actors

Abstract: Recent resting-state fMRI studies have revealed neuroplastic alterations after long-term training. However, the neuroplastic changes that occur in professional traditional Chinese Pingju opera actors remain unclear. Twenty professional traditional Chinese Pingju opera actors and 20 age-, sex-, and handedness-matched laymen were recruited. Resting-state fMRI was obtained by using an echo-planar imaging sequence, and two metrics, amplitude of low frequency fluctuation (ALFF) and regional homogeneity (ReHo), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Neuroplasticity of professional opera performers was studied by Zhang et al ( 2018 ). Professional traditional Chinese Pingju performers, as compared with laymen, demonstrated increased regional homogeneity (ReHo) in the left anterior insula; decreased ReHo in the right middle occipital gyrus, bilateral calcarine, and superior occipital gyri and cuneus; and reduced ALFF in the bilateral cuneus and calcarine gyrus, indicating superior multidimensional performance on dancing, emotional representation, and face and music perception.…”
Section: Occupational Neuroplasticitymentioning
confidence: 99%
“…Neuroplasticity of professional opera performers was studied by Zhang et al ( 2018 ). Professional traditional Chinese Pingju performers, as compared with laymen, demonstrated increased regional homogeneity (ReHo) in the left anterior insula; decreased ReHo in the right middle occipital gyrus, bilateral calcarine, and superior occipital gyri and cuneus; and reduced ALFF in the bilateral cuneus and calcarine gyrus, indicating superior multidimensional performance on dancing, emotional representation, and face and music perception.…”
Section: Occupational Neuroplasticitymentioning
confidence: 99%
“…Although the mechanisms of this observation are yet to be elucidated, there is accumulating evidence revealing how particularly exercise, a planned and structured sub-set of physical activity performed at increased energy expenditure 5 , seems to induce both acute and chronic adaptations in the brain. Long-term endurance training of animals evoked angiogenesis, neurogenesis and enhanced synaptic plasticity 6 8 . Studies examining humans found expression of the brain-derived neurotrophic factor (BDNF) and increases in hippocampal volume occurred following several weeks of aerobic exercise 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The time series were transformed to frequency domains by fast Fourier transform, the power spectrum was obtained. The square root was calculated at each frequency of the power spectrum, the averaged square root was obtained across 0.01-0.08 Hz, and this averaged square root was taken as the (ALFF; Zhang et al, 2018).…”
Section: Amplitude Of Low-frequency Fluctuation (Alff) Calculationmentioning
confidence: 99%
“…To date, several studies have examined dance training related changes in spontaneous brain activity in the human brain. For instance, a previous study found that professional traditional Chinese Pingju actors showed decreased ALFF in the bilateral calcarine gyrus and cuneus, decreased ReHo in the bilateral superior occipital and calcarine gyri (Zhang et al, 2018). The abovementioned reports indicate that these three measures are reliable and sensitive methods for examining the effects of various dance training on neurofunctional alterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation